HYBRID LEARNING AND COMMUNICATION PATTERNS OF RELIGIOUS TEACHERS IN IMPROVING STUDENTS' UNDERSTANDING AT MAN 1 BONE - Riswandi Adriansyah; Astuti Astuti; Kurniati Abidin (Education Studies and Teaching Journal (EDUTECH), 2025)
This study explores the implementation of hybrid learning and the communication patterns of religious teachers in enhancing students' understanding at State Islamic Senior High School (MAN) 1 Bone. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation, and analyzed with reduction, presentation, and conclusion techniques. Findings reveal that hybrid learning, which integrates technology, models, and approaches, fosters diverse learning methods that motivate students and enhance comprehension. Teachers’ two-way and multi-directional communication, both face-to-face and via digital platforms (WhatsApp, Google Classroom, Zoom), supports open and participatory interactions, positively influencing understanding. Positive impacts include higher student engagement, easier access to materials, and stronger interpersonal relationships, though challenges remain in internet connectivity, teachers’ technological readiness, and limited emotional interaction online. The study highlights the need for teacher training in digital pedagogy and communication, alongside infrastructure support, to optimize and sustain hybrid learning.